2017
DOI: 10.18488/journal.80.2017.42.42.50
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Appraisal of Problems and Prospects of Fertilizer Use for Agriculture on the Environment in Mbieri, Mbaitoli Local Government Area, Imo State Nigeria

Abstract: Article HistoryThis study appraises the spatial problems and prospects of fertilizer use in agriculture on the Environment in Mbieri, Mbaitoli Local Government Area of Imo State. Structured questionnaires were sampled in each villages randomly selected from the seven autonomous communities of Amaike-Mbieri, Awo Mbieri, Ezi-Mbieri, Ihitte IsiMbieri, Obazu Mbieri, Obi-Mbieri and Umueze-Mbieri for collection of data. The data were analysed using descriptive statistical tools of tables, charts and graphs. The outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The impacts of emerging agricultural practices have been seen in greater incidences of soil erosion, land degradation, and increased levels of pathogens, nutrients, and chemicals in surface water. This is in line with the findings of Chikwendu et al (2017) and Kughur et al (2015) who observed that intensive agricultural practices in Nigeria destroy soil nutrients and soil quality leading to soil erosion, pollution of water bodies, and loss of biodiversity. Deforestation has been a major fallout of land-use change in southern Nigeria.…”
Section: Land-use Changes In Southern Nigeriasupporting
confidence: 91%
“…The impacts of emerging agricultural practices have been seen in greater incidences of soil erosion, land degradation, and increased levels of pathogens, nutrients, and chemicals in surface water. This is in line with the findings of Chikwendu et al (2017) and Kughur et al (2015) who observed that intensive agricultural practices in Nigeria destroy soil nutrients and soil quality leading to soil erosion, pollution of water bodies, and loss of biodiversity. Deforestation has been a major fallout of land-use change in southern Nigeria.…”
Section: Land-use Changes In Southern Nigeriasupporting
confidence: 91%